Synthesis, Characterization and Evaluation of Antibacterial Efficacy, Antioxidant Potential of Silver nanoparticle using Myrica nagi leaf extract - Preeti Panthari; Pranauv Balaji; Monika Joshi; Harsha Kharkwal (International Journal of Phytomedicine, 2014)
In the present work, we report an environment friendly biosynthesis of silver nanoparticles using ethanolic extract of Myrica nagi leaves. This endangered tree with wide medicinal applications has rich amount of anti-oxidants along with other classes of chemicals. Various therapeutic compounds such as myricanol, myricanone, myricetrin, sitosterol, taraxerol are isolated from the various parts of the plant. In this process, reduction of Silver ions to silver nanoparticles was achieved by a bioactive compound from Myrica Nagi plant. The synthesized nanoparticles were characterized using UV-visible spectrophotometer, Dynamic Light Scattering (DLS), Scanning Electron Microscopy (SEM) and FTIR. The formation, stability and particle size of Ag nanoparticles was characterized using UV-Vis spectrophotometer and Dynamic Light Scattering. Scanning Electron Microscopy (SEM) micrograph shows a uniform distribution of the particles with an average size of 50-60nm. FTIR analysis confirms the presence of hydroxyl, carboxyl and phenolic functional groups. Further, the antimicrobial activity of silver nanoparticles shows that these nanoparticles can be used as effective growth inhibitors against E. coli, S.aureus and S. pyogenes with zone of inhibition of 1.2, 1.3 and 0.8 cm respectively. The synthesized silver nanoparticle have a potential application in targeted drug delivery, wound healing and other medical applications. The antioxidant activity of AgNPs imparted by plant components was evaluated using DPPH assay and found to be comparable to standard ascorbic acid.